CHOICE OF THE INITIAL TREATMENT FOR MILD TO MODERATE ARTERIAL HYPERTENSION IN MOSCOW PRIMARY PRACTICE - S. V. Gatsura; O. A. Gatsura; A. N. Golosova (Рациональная фармакотерапия в кардиологии)
Aim. To assess the choice of initial pharmacotherapy of uncomplicated mild to moderate arterial hypertension (HT) in Moscow primary care as well as to clear up the influence of regulatory measures on this choice.Material and methods. Results of two similar surveys conducted in 2011-2012 (452 respondents) and 2013-2014 (273 respondents) were compared to estimate preferences of Moscow primary care physicians regarding initial antihypertensive agents for therapy of uncomplicated mild to moderate HT taking into consideration an influence of regulatory requirement to prescribe medicinal products by international nonproprietary name (INN) since July 2012. All participants were proposed to write down their preferred antihypertensive agents for initial mono- or combined therapy of mild to moderate HT with moderate cardiovascular risk and absence of compelling indications.Results. Angiotensin converting enzyme inhibitors (ACEI) remained the leading class of antihypertensive agents, though their popularity slightly but significantly declined from 44.4% in 2011-12 to 37.2% in 2013-14 (р<0.05). Angiotensin receptor blockers partially displaced the leaders and increased their popularity from 11.3% in 2011-12 to 18.0% in 2013-14 (р<0.01). ACEI/diuretic combination remained on the 3rd position (16.4% and 15.3% respectively). Beta-blockers and diuretics as monotherapy shared 4th and 5th places in this rating. Calcium channel blockers popularity among Moscow prescribers remained unchanged and poor – 2.1%. The most popular medicine by trade name was Noliprel, perindopril/indapamide fixed combination, – 14.0% and 13.7% of respondents in 2011-12 and 2013-14, respectively. The share of medicine products recommended by INN went up from 11.9% to 22.8% among top-10 popular medications (р<0.01).Conclusion. Blockers of renin-angiotensin-aldosterone system remain the leading drugs for the initial treatment of uncomplicated mild to moderate HT without compelling indications among Moscow primary care physicians. Regulatory requirement to prescribe medicinal products by INN was associated with significant increase in the share of drugs recommended by INN, though this effect was less than expected one.